Evaluation of Phytochemicals and Bioactive Properties in Mangrove Associate Suaeda monoica Forssk. ex J.F.Gmel. of Indian Sundarbans - Roy, Madhumita; Dutta, Tapan K. (Frontiers in Pharmacology, 2021)
Suaeda nudiflora (Willd.) Moq. (Chenopodiaceae), a mangrove associate and ethno-medicinal herb of Indian Sundarbans, was investigated as a promising source of bioactive compounds. Various polar and nonpolar solvent extracts of the leaf and root-shoot parts of the plant exhibited antioxidant, antibacterial, antifungal, allelopathic, mosquitocidal, antihaemolytic and antidiuretic potential. Moreover, to meet pharmacological requirements, the antioxidant ability of the plant was validated by both chemical and biological analyses. Extraction yield and presence of different phytochemicals like phenolics, flavonoids, tannins and saponins were compared in various solvent-extracted fractions. Principle component analysis revealed that the antioxidant property present in different extracts maintained a positive correlation with the occurrence of polyphenols (phenolics, tannins and flavonoids). Biochemical evaluation, HPLC examination and GC-MS analysis showed a differential level of the presence of various phytochemicals in different solvent extracts. In contrast to mosquitocidal, antioxidant, antihaemolytic and phytotoxic properties which were observed to be dominant in polar solvent extracts, maximum antibacterial potency was detected in nonpolar n-hexane fractions. Overall, the plant extract is nontoxic in nature and a dose amounting to 3000 mg/kg was well tolerated by Swiss albino mice. A combination of HPLC and GC-MS analyses showed the presence of a large number of structurally diverse phytochemicals, many of which had already been reported as insecticidal, mosquitocidal, antibacterial, herbicidal, antidiuretic, antioxidant and anti-haemolytic compounds. All these findings support that the least explored traditional edible medicinal mangrove associate S. nudiflora is enriched with multiple bioactive molecules and may be considered as one of the richest sources of various lead molecules of pharmaceutical importance.